Technical Efficiency’s Nonparametric Analysis of Ecuadorian Saving and Credit Cooperatives before and during the Pandemic - Carlos S. Torres-Inga; Cristina Velasco-Heras; A. Javier Aguirre-de Juana; Guillermo E. Guevara-Viera; Raúl V. Guevara-Viera (Economies, 2022)
Ecuador’s credit unions or COACs play a key role inside the local economy, and the pandemic period has shown the weakness of the entities. Understanding the efficiency of the country’s largest COACs and the different factors related to it can provide important information for policymakers and the sector in general. Therefore, our main goal was the evaluation of technical efficiency and the factors that influenced it during the years from 2009 to 2020 which included the pandemic period. For this, the DEA model was applied with production and intermediation focus, and this was applied to 19 COACs from the first segment of the sector. Findings reveal that the level of technical efficiency was larger in the pre-pandemic than the pandemic period. Efficient credit unions were characterized by higher profitability, low levels of liquidity and portfolio coverage, and a high rate of financial intermediation, among others, through the pre-pandemic period; however, debt restructuring was one the most important characteristics of nonefficient Credit Unions. The most important contribution of this study is the possible projection of different decisions that will allow the COACs to improve their role in the system given all the difficulties that the pandemic is causing around the world.